Verletzungsprävention durch Verbesserung der neuromuskulären Bewegungskontrolle - Hottenrott, K.; Gronwald, T.; Neumann, G. (Sport-Orthopädie - Sport-Traumatologie, 2011)
The fact that existing prevention strategies still cause sustained high injury rates and health disorders in performance sports should result in a critical view on the current methods. In the last 20 years, research in soccer showed that injury rates could not be reduced despite the use of several interventions with different motor control techniques. Own investigations prove that prolonged peripheral and central fatigue is a predictor for the development of overload damage and injuries. EEG-data indicate a relation between the activity of the motor system in the brain, the sensory feedback control system and muscular fatigue. Furthermore, this data implies that injury prevention can be achieved through an optimization of the neuromuscular control of joint movements. Apparently, firm movement patterns in combination with different pressure situations and highly intensive load situations have to be trained in order to optimize motor control and to decode abnormal central regulations. To prevent abnormal regulations, the link between cognition and action should be the basis for a new kind of sport-specific athletic training. The acquired exercises should be part of every warm-up routine to facilitate a faster and more appropriate reaction to new situations.